2002
DOI: 10.1152/ajpgi.00534.2001
|View full text |Cite
|
Sign up to set email alerts
|

H+-peptide cotransport in the human bile duct epithelium cell line SK-ChA-1

Abstract: This study describes for the first time the presence of H+-peptide cotransport in cells of the bile duct. Uptake of [glycine-1-14C]glycylsarcosine ([14C]Gly-Sar) in human extrahepatic cholangiocarcinoma SK-ChA-1 cells was stimulated sevenfold by an inwardly directed H+ gradient. Transport was mediated by a low-affinity system with a transport constant ( K t) value of 1.1 mM. Several dipeptides, cefadroxil, and δ-aminolevulinic acid, but not glycine and glutathione, were strong inhibitors of Gly-Sar uptake. SK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 25 publications
(42 reference statements)
1
37
1
2
Order By: Relevance
“…Human PepT1 (hPepT1), which mediates this peptide transport activity (6,8,9), cotransports peptides with H ϩ (12,17,21,24) and has a broad specificity including many di/tripeptides and peptide-derived drugs (42,43). Functional expression of hPepT1 in Xenopus laevis oocytes induces H ϩ -dependent peptide-transport activity, therefore recapitulating the transport activity observed in natural gut epithelia (30,40).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Human PepT1 (hPepT1), which mediates this peptide transport activity (6,8,9), cotransports peptides with H ϩ (12,17,21,24) and has a broad specificity including many di/tripeptides and peptide-derived drugs (42,43). Functional expression of hPepT1 in Xenopus laevis oocytes induces H ϩ -dependent peptide-transport activity, therefore recapitulating the transport activity observed in natural gut epithelia (30,40).…”
mentioning
confidence: 92%
“…PepT1 is mainly expressed in brush border membranes (BBMs) of enterocytes in small intestine, in proximal tubular cells of the S1 segment of kidney, and in bile duct epithelial cells (1,9,17,34,35,38). Expression of PepT1 mRNA or protein is low (46) or not detected (25,34) in the colon but is transiently expressed in normal rat colon cells during the first few days after birth (35).…”
mentioning
confidence: 99%
“…The specificity of hPepT1 is broad and includes many di-and tripeptides in addition to various peptide-derived drugs (3)(4)(5)(6)(7)(8). PepT1 is mainly expressed in brush-border membranes of enterocytes in the small intestine, in proximal tubular cells of the S1 segment of the kidney, and in bile-duct epithelial cells (4,5,(9)(10)(11)(12)(13)(14)(15). By contrast, in the colon, expression of PepT1 mRNA and protein is low (16) and sometimes cannot be detected (10,15,17).…”
Section: Introductionmentioning
confidence: 99%
“…Gonzalez et al reported that human pancreatic carcinoma cell lines AsPC-1 and Capan-2 also possess peptide transport activity and express PEPT1 (13). Subsequently, our group (11) and Knütter et al (14) reported that human gastric cancer cell line MKN45, human osteosarcoma cell line MG-63, human bladder cancer cell line T24, and human extrahepatic cholangiocarcinoma cell line SKChA-1 also exhibit peptide transport activity. These findings suggest that the PEPTs may be a promising target for cancer imaging using PET.…”
mentioning
confidence: 98%